Efforts to Improve the Performance of Medical Personnel through Perceived Organizational Support - Ranihusna, Desti; Ulfa, Unzilla Ainun; Wulansari, Nury Ariani; Wartini, Sri (JDM (Jurnal Dinamika Manajemen), 2021)
The Universal Health Coverage program was implemented in 2014, have several impacts, one of the impacts is to increase patient visits to first-level or upper-level health facilities. Patient visits data used to compile the medical performance that will be assessed and evaluated byÃ‚Â Dinas KesehatanÃ‚Â Central Java Province. The average patient visits in several working of Public Health Center known asÃ‚Â BalkesmasÃ‚Â in Central Java Province show a significant decrease. Meanwhile, the COVID-19 pandemic makesÃ‚Â BalkesmasÃ‚Â employees concerned about their health safety and their familyÃ¢â‚¬â„¢s health safety. Therefore, organizational support and work engagement are very important to feel comfortable and safe at work to improve their performance.Ã‚Â The purpose of the research is to examineÃ‚Â BalkesmasÃ‚Â employeesÃ¢â‚¬â„¢ performance system through perceived organizational support and work engagement. This research methodology is quantitative research and used questionnaires distributed to 86 employees.Ã‚Â Research hypotheses were tested used the structural equation model method with the SmartPLS 3.0 program. All of the research hypotheses are acceptable and show a significant effect, so it can be concluded that the better of perceived organizational support and the higher of work engagement, employees' performanceÃ‚Â will be increased.Ã‚Â